Germination of Dimorphic Seeds and Seedling Growth of Two Desert Grasses - Kumar, Arun; Joshi, M C (Annals of Arid Zone, 2016)
The present study shows that dimorphic seeds are found in O. biflorus and O. prieurii. Seed output is found more in O. prieurii while the production of large seeds is higher in C. biflours. Large seeds of O. bijlorus. show more percentage germination than small seeds while the the case is reverse with O. prieurii. Production of large seeds in both grasses produce greater shoot and root length and also the dry matter than those from the small seed fraction. O.biflorus is of gregarious occurrence. in this area which may be attributed to its greater 'large' seed output and germination percentage of both large and small seeds in comparison to O. prieurii.